The Comparison of ‘Iddah and Ihdad in the Shafi’i and Hanafi School - Yusroh; Haaniyatur Roosyidah; M. Arif Hakim (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This article discusses comparisons that include the similarities and differences between the Shafi'i and Hanafi Schools in interpreting 'iddah and ihdad with a literature review. The method used in uncovering the purpose of this research is literature studies with research sources in the form of various books, articles, and other documents. The data were then analyzed using a comparative descriptive and a qualitative approach. The study results show the differences between the Shafi'i and Hanafi Schools in interpreting 'iddah and ihdad. Apart from the definition of 'iddah and calculating the period of 'iddah, these two schools have some similarities. The difference between these two Schools is in the meaning of the quru' during the 'iddah period for a woman divorced by her husband while her menstruation is not interrupted. The next difference is the prohibition for women in ihdad to leave the house. The two schools of thought both allow women to leave the house for ihdad, but the Hanafi school tends to limit it to working only to make a living, not for other needs, while the Shafi'i school is more relaxed, in the sense of leaving the house for a particular purpose. Another difference is that the Hanafi School requires divorced women to perform 'ihdad, whereas according to the Shafi'i School, it is only recommended. For women who work (career), if she is required to perform 'iddah or ihdad, then she continues to do so as long as she knows the limits she has to go out and does not violate the abovementioned provisions.